P168 Reduced Gas Transfer (tlco) Predicts Poor Outcome In Patients With Pulmonary Hypertension And Heart Failure With Preserved Ejection Fraction. (10th November 2014) - Hussain, N; Ramjug, S; Billings, C; Hurdman, J; Elliot, CA; Condliffe, R; Kiely, DG
Abstract : Rationale: There is limited data on predictors of survival in patients with Pulmonary Hypertension (PH) in the context of Heart Failure and Preserved Ejection Fraction (HF-pEF). Simple non-invasive tests to aid the physician in prognostication would be valuable. The aim of this study was to examine demographic and non-invasive predictors of outcome in PH-HF-pEF in a large well phenotyped PH registry. Method: In the ASPIRE Registry (Hurdman J et al Eur Resp J, 2012), 1737 consecutive, incident, treatment-naıve patients with suspected PH underwent diagnostic evaluation between February 2001 and 2010. Patients were diagnosed as PH-HF-pEF if no other causes of PH could be identified and they fulfilled the following criteria: signs and symptoms of heart failure; mean pulmonary artery pressure ≥25 mmHg at rest and pulmonary arterial wedge pressure >15 mmHg by RHC; preserved left ventricular systolic function (ejection fraction ≥50%) by echocardiography or CMR. Predictors of survival were assessed using forward stepwise Cox regression analysis. Variables with a p-value Results: 98 patients who fulfilled the diagnostic criteria for PH-HF-pEF were identified. Maximum duration of follow-up was 10 years with a mean follow up 4.9 ± 2.3 years, during which 33 (34%) patients died. After multivariate analysis, only ISWT distance HR 0.99 CI (0.99–1.00) and TLCO HR 0.96 CI(0.94–0.98) at baseline, were predictors of outcome (p < 0.01). Median predicted TLCO in the PH-HF-pEF population was 65%. The 5-year survival in those with a TLCO <65% predicted was 60%, compared with 85% in those whose TLCO was ≥65% (p < 0.01). Conclusions: Simple non-invasive testing such as TLCO and exercise capacity measured by the ISWT predict outcome in patients with PH-HF-pEF.